Thermal insulating products for building equipment and industrial installations. In-situ formed sprayed rigid polyurethane (PUR) and polyisocyanurate foam (PIR) products. Specification for the rigid foam spray system before installation Part 1, (31st January 2013) - British Standards Institution,
No abstract available